The existence of Reba - Bertolomeus Loji Sua (International Conferences on Educational, Social Sciences and Technology)
This article explains about the existence of ‘Reba’ as a culture in the midst of easy and instant modernization, especially in getting information supported by modern technology. So far Bajawa people still maintain and revive 'Reba' so that the culture of 'Reba' still shows its existence in the middle of the current globalization and modernization. ‘Reba’ is an unifying symbol for generations of Bajawa people that cannot be replaced with other cultures because the culture of 'Reba' has history and philosophical value that are only understood by Bajawa people.The culture of 'Reba' is not only for an annual celebration of gratitude, but also as as a venue for family gathering coming from distant places. The end of this article will also explain about moral values of the culture of ‘Reba’ so that ‘Reba’ can be maintained as a celebration of gratitude toward ancestors in the midst of modernization.